2021
DOI: 10.1016/j.jsat.2020.108222
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented need and recommendations for harnessing data to guide future policy and practice for opioid use disorder treatment following COVID-19

Abstract: The COVID-19 pandemic struck in the midst of an ongoing opioid epidemic. To offset disruption to life-saving treatment for opioid use disorder (OUD), several federal agencies granted exemptions to existing federal regulations. This included loosening restrictions on medications for OUD (MOUD), including methadone and buprenorphine. In this commentary, we briefly review policy and practice guidelines for treating OUD prior to the onset of the COVID-19 pandemic. We then outline specific MOUD treatment policy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The unprecedented change in OTP regulations during the COVID-19 pandemic provides a unique opportunity for research and, potentially, regulatory reform (Hatch-Maillette et al, 2020;Livingston et al, 2020). Consistent with other reports (Morin et al, 2021), we found that the absolute percent of positive opioid and non-opioid drug tests increased following the federal variance that allowed more methadone take-out doses, but we also found that this result cannot be fully attributed to alterations in the take-out schedule.…”
Section: Discussionsupporting
confidence: 88%
“…The unprecedented change in OTP regulations during the COVID-19 pandemic provides a unique opportunity for research and, potentially, regulatory reform (Hatch-Maillette et al, 2020;Livingston et al, 2020). Consistent with other reports (Morin et al, 2021), we found that the absolute percent of positive opioid and non-opioid drug tests increased following the federal variance that allowed more methadone take-out doses, but we also found that this result cannot be fully attributed to alterations in the take-out schedule.…”
Section: Discussionsupporting
confidence: 88%
“…These included the Drug Addiction Treatment Act of 2000, Title 42 of the Code of Federal Regulations Part 8 (42 CFR 8) for OTPs, and the Federal Ryan Haight Online Pharmacy Consumer Protection Act of 2008. These regulations restricted prescribing and dispensing controlled substances for tele-MOUD and included requirements for in-person encounters to prescribe MOUD [ 49 ]. In addition, reimbursement restrictions and variations across public and private payers created significant complexities.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, questions remain about the relationship between the continuation or expansion of these PHE flexibilities, telehealth service use trends, and effective treatment for individuals with OUD. 21 The findings from this analysis make a compelling argument that flexibilities in the workplace should be matched by flexibilities in the delivery of health care via telehealth, although the potential for subsequently creating new barriers to treatment should be carefully considered. On one hand, as workplaces continue to support hybrid working environments, 22 including a broader geographic range of behavioral health providers in employer-based insurance plans via telehealth may be an important strategy to expand employees' access to behavioral health services, especially given current constraints in the behavioral health provider workforce.…”
Section: Discussionmentioning
confidence: 98%